Studi Ergonomi dan Pengaruh Persepsi Ergonomi Kerja terhadap Efisiensi Pekerja Manual Handling di PT Karya Limpah Berkah - Muhammad Harfian Nuruludin; Ida Kusnawati Tjahjani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Manual Material Handling (MMH) activities are predominantly performed manually and carry the potential to cause musculoskeletal disorders if executed using non-ergonomic postures. Such conditions can reduce work efficiency, making the application of ergonomic principles crucial. This study aims to analyze the impact of ergonomic perception on work efficiency and to evaluate ergonomic risk levels among manual handling workers at PT Karya Limpah Berkah. A quantitative approach—employing both descriptive and associative methods—was used, with a total sampling of 15 workers. Data were collected through observation, documentation, interviews, and questionnaires. Ergonomic risks were evaluated using REBA, RULA, and NIOSH methods, while the relationships between variables were analyzed using Pearson correlation and simple linear regression via SPSS. The results indicate that ergonomic perception has a positive and significant effect on work efficiency (r = 0.894; p = 0.000; R² = 0.800). The highest risk levels were identified in the staffing section (REBA = 10, RULA = 7, LI = 3.08). These findings highlight the need to improve work postures and lifting activities, particularly within the staffing section.